Innovation strategy, quality and performance in the service sector - Vélez Osorio, Iris María (2018)
STRUCTURED ABSTRACT1)      Objective: The present research aims to identify how the innovative strategy affects the organizational performance and quality in processes of service sector organizations in Colombia, taking into account their production process improvements, and organizational methods. 2)      Method: It was used the Survey of Development and Technological Innovation (EDIT) created by the Administrative National Department of Statistics DANE, collecting 19 subsectors and a total of 5.848  companies. 3)      Theoretical Framework: This research is settled in the competitive strategy, resource based view of the firm, and innovation theory. 4)      Results: Finding that the innovative strategy benefits the improvement in the quality of processes and this in turn becomes the engine of organizational performance. 5)      Conclusions: The Colombian services sector represents an important sector for economic growth, the innovative strategy becomes the determining factor to create value in the processes and offer quality services that promote sector organizations as the best in each area. However, for the smaller organizations in each service sector, higher levels of investment are required that allow them to make improvements in production methods and continuous organizational methods; investment in scientific, technological and innovation activities must have all sources of financing that translate into substantial changes in services. 6)      Contributions: This research allows to understand for the service sector and their particular context the importance to have an innovation strategy with scarce resources to improve performance and quality. The innovation strategy affects both cases, the organizational performance is better in the organizations of the service sector, which means that their sales levels increase every time they generate substantial improvements in methods of providing services, distribution, delivery or logistic system, which we have called production methods, and second, in the quality of processes of these companies, improving routines within the organization, internal improvements called improvements in organizational methods are generated improvements in the quality of each process, this effect for organizations is translated into certifications that impact on the final customer who acquires the service.Key Words: Innovation Strategy, Innovation, Organizational Performance, Service Industry, Quality Management.JEL: M1, M10, L8 REGULAR ABSTRACT: The present research aims to identify how the innovative strategy affects the organizational performance and quality in processes of service sector organizations in Colombia, taking into account their production process improvements, and organizational methods. It was used the Survey of Development and Technological Innovation (EDIT) created by the Administrative National Department of Statistics DANE, collecting 19 subsectors and a total of 5.848  companies. Finding that the innovation strategy benefits the improvement in the quality of processes and this in turn, becomes the engine of organizational performance. The Colombian services sector represents an important sector for economic growth, the innovative strategy becomes the determining factor to create value in the processes and offer quality services that promote sector organizations as the best in each area. However, for the smaller organizations in each service sector, higher levels of investment are required that allow them to make improvements in production methods and continuous organizational methods; investment in scientific, technological and innovation activities must have all sources of financing that translate into substantial changes in services.Key Words: Innovation Strategy, Innovation, Organizational Performance, Service Industry, Quality Management.JEL: M1, M10, L8